2021
DOI: 10.2196/30251
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging Transfer Learning to Analyze Opinions, Attitudes, and Behavioral Intentions Toward COVID-19 Vaccines: Social Media Content and Temporal Analysis

Abstract: Background The COVID-19 vaccine is considered to be the most promising approach to alleviate the pandemic. However, in recent surveys, acceptance of the COVID-19 vaccine has been low. To design more effective outreach interventions, there is an urgent need to understand public perceptions of COVID-19 vaccines. Objective Our objective was to analyze the potential of leveraging transfer learning to detect tweets containing opinions, attitudes, and behavio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 35 publications
0
27
0
Order By: Relevance
“…Therefore, it would be common to find a portion of the respondents who got vaccinated although they are against the vaccines. Most of the studies related to people's attitudes towards the vaccines reviewed in the literature were done before obligating citizens to get vaccinated (e.g., Wilson &Wiysonge, 2020;Liu &Liu, 2021;Lueck & Spiers, 2021;Baeza-Rivera et. al., 2021;Matute et.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it would be common to find a portion of the respondents who got vaccinated although they are against the vaccines. Most of the studies related to people's attitudes towards the vaccines reviewed in the literature were done before obligating citizens to get vaccinated (e.g., Wilson &Wiysonge, 2020;Liu &Liu, 2021;Lueck & Spiers, 2021;Baeza-Rivera et. al., 2021;Matute et.…”
Section: Discussionmentioning
confidence: 99%
“…Siru Liu, Jili Li, and Jialin Liu (2021) analyzed 2,678,372 tweets related to COVID-19 vaccines from 841,978 unique users and annotated 5000 tweets posted over a 3-month period (from November 1, 2020 to January 31, 2021). Results have shown that the prevalence of tweets containing positive behavioral intentions increased over time (Liu, Li, & Liu, 2021).…”
Section: Vaccine-related Content On Social Mediamentioning
confidence: 99%
See 1 more Smart Citation
“…( 2021 ) 2021 Understanding the public attitudes towards COVID19 Amazon Comprehend ML 1M Tweets Mar20–Jan21 No English TF-IDF K-means clustering N/A Kumaresh ( yyy ) 2021 Analysing public sentiment regarding Covid-19 vaccines VADER ML 1200 Tweets N/A No English TF-IDF Naïve Bayes, LR India Liu et al. ( 2021 ) 2021 Understanding public perceptions of COVID-19 vaccines Manual annotation ML/DL 5000 Tweets Nov20–Jan21 No English TF-IDF BERT, LR, RF, SVM N/A Aygün et al. ( 2021 ) 2021 Analyzing public sentiments related to COVID-19 vaccines Aspect-Based DL 928,402 Tweets Nov20–Mar21 No English, Turkish TF-IDF, Word2Vec BERT 8 Countries Yang and Sornlertlamvanich ( 2021 ) 2021 Investigating Public Perception of COVID-19 Vaccine TextBlob ML 190,000 Tweets Dec20–Jun21 No ...…”
Section: Related Workmentioning
confidence: 99%
“…With the rise in computational power, many researchers were able to apply BERT to COVID-19 and vaccination content in English and test its results against older methods, such as bidirectional long-short term memory, support vector machines, and naïve Bayes. BERT-based architecture proved to be superior both for binary sentiment, relevance, or misinformation classification [ 9 , 13 , 19 , 28 ] and for tertiary stance or sentiment classification [ 14 , 17 , 19 ], which prompted us to choose such architecture for our research.…”
Section: Introductionmentioning
confidence: 99%